Comparative transcriptome analysis reveals nicotine metabolism is a critical component for enhancing stress response intensity of innate immunity system in tobacco - Song, Zhongbang; Wang, Ruixue; Zhang, Hongbo; Tong, Zhijun; Yuan, Cheng; Li, Yong; Huang, Changjun; Zhao, Lu; Wang, Yuehu; Di, Yingtong; Sui, Xueyi (Frontiers in Plant Science, 2024)
The pyridine alkaloid nicotine acts as one of best-studied plant resistant traits in tobacco. Previous research has shown that NtERF199 and NtERF189, acting as master regulators within the NIC1 and NIC2 locus, quantitatively contribute to nicotine accumulation levels in N. tabacum. Genome editing-created Nic1(Nterf199) and Nic2 (Nterf189) double mutant provides an ideal platform for precisely dissecting the defensive role of nicotine and the connection between the nicotine biosynthetic pathway with other putative metabolic networks. Taking this advantage, we performed a comparative transcriptomic analysis to reevaluate the potential physiological and metabolic changes in response to nicotine synthesis defect by comparing the nic1nic2 and NIC1NIC2 plants. Our findings revealed that nicotine reduction could systematically diminishes the expression intensities of genes associated with stimulus perception, signal transduction and regulation, as well as secondary metabolic flux. Consequently, this global expression reduction might compromise tobacco adaptions to environmental fitness, herbivore resistances, and plant growth and development. The up-regulation of a novel set of stress-responsive and metabolic pathway genes might signify a newly established metabolic reprogramming to tradeoff the detrimental effect of nicotine loss. These results offer additional compelling evidence regarding nicotine's critical defensive role in nature and highlights the tight link between nicotine biosynthesis and gene expression levels of quantitative resistance-related genes for better environmental adaptation.